Relación entre el gasto público en asistencia social ejecutado por la Municipalidad Provincial de Maynas y la pobreza monetaria en Iquitos 2014-2023 - Eca Panta, César Antonio (2025)
Public spending on social assistance involves a set of actions aimed at achieving social development objectives, encompassing protection, assistance, development of social and economic capabilities, and the promotion of equal opportunities for people. This research contributes to the advancement of knowledge on public management, by providing empirical data on the relationship between social assistance spending and monetary poverty, serving as a basis for future research and for the design of public policies. After applying a quantitative and correlational analysis to a total of forty quarterly records, it was determined that there is a weak negative relationship of 26.74% between public spending on social assistance executed by the Provincial Municipality of Maynas, expressed in real values, and Iquitos´ monetary poverty, in period 2014-2023. Furthermore, a weak negative relationship of 28.71% was found between public spending on social assistance for the protection of populations at risk executed by the institution, expressed in real values, and Iquitos´ monetary poverty. However, no relationship was found between public spending on social assistance for the development of social and economic capabilities and monetary poverty.